Pengaruh Gaya Kepemimpinan dan Disiplin Kerja terhadap Kinerja Pegawai Kantor Kecamatan Cambai Kota Prabumulih - Ellisyah Mindari (Program Magister Manajemen Indo Global Mandiri University, 2020)
Purpose. Formulations of the problem in this research is there any influence leadership style and discipline to employee performance. Design/methodology. This research was associative. The location of this study addressed at Jalan Sudirman No. 01 KM. 10 Village Cambai District of Cambai Prabumulih zip code 31141. The sample in this study as many as 50 people, with saturated Sampling analysis techniques. The data used are primary data. Data were collected through questionnaires. Analysis of the data used is the qualitative and quantitative analysis. Techniques using multiple linear regression analysis, F test (simultaneous) and t test (partial). Finding. Results of the testing that has been done from this study indicate that the multiple linear regression calculation results obtained Y = 1.881 + 0,391X1 + 0,354X2, for the F test obtained Fhitung (9.175)> F table (3.20), meaning that there is influence leadership style and discipline work on employee performance SDOs Cambai Prabumulih, for the t test of leadership style variable (X1) obtained t (4.333)> t table (2.011), meaning that the leadership style partially influence on employee performance. T test variable work discipline (X2) obtained t (2.545)> t table (2.011), meaning that the work discipline partially influence on employee performance.